THE EVALUATION OF THE PROSTHETIC PREPARATIONS FINISH LINES FOR PROVISIONAL CROWNS WITH THE IMPACT ON PERIODONTAL HEALTH - Simona Ioana Hategan; Alina-Luminita Belea; Alina Doina Tanase; Andrei-Mihai Gavrilovici; Emanuela-Lidia Petrescu; Liviu Marsavina; Cosmin Sinescu; Meda-Lavinia Negrutiu; Marius-Ciprian Manole (Romanian Society of Oral Rehabilitation, 2024)
Aim of the study: The aim of this study is to evaluate the resistance of different marginal fit geometries for a provissional fixed dental prothesis, which can have an impact on the periodontal health. Materials and methods: Acording to the principles of the tooth preparation, four types of marginal design were made: feather edge, rounded shoulder, chamfer and heavy chamfer. Using a direct technique, prepared teeth were poured into metal abutments, temporary composite resin crowns were made and cemented. All four abutments were analyzed using theoretical and experimental methods. Results: The results obtained from the mechanical tests were more reliable than those obtained from numerical analyses. A chamfer marginal finish line a pre prosthetic periodontal therapy can have greater impact on the soft tissue healing process. Conclusions: These preliminary studies enhance the idea of ​​differentiating preparations for distinctive alternative prosthetic treatment plans.